Notice: We are no longer accepting new posts, but the forums will continue to be readable.
Maxwell Equations deriving the Dirac Equation Chapt15.37 base equation of all physics is Area = LxW from Maxwell Equations #1134 New Physics #1254 ATOM TOTALITY 5th ed
Jan 4, 2013 6:02 PM
Alright, these are the 4 symmetrical Maxwell Equations with magnetic monopoles:
div*E = r_E div*B = r_B - curlxE = dB + J_B curlxB = dE + J_E
Now to derive the Dirac Equation from the Maxwell Equations we add the lot together:
div*E = r_E div*B = r_B - curlxE = dB + J_B curlxB = dE + J_E ________________
div*E + div*B + (-1)curlxE + curlxB = r_E + r_B + dB + dE + J_E + J_B
Now Wikipedia has a good description of how Dirac derived his famous equation which gives this:
(Ad_x + Bd_y + Cd_z + (i/c)Dd_t - mc/h) p = 0
So how is the above summation of Maxwell Equations that of a generalized Dirac Equation?
Well, the four terms of div and curl are the A,B,C,D terms. And the right side of the equation can all be conglomerated into one term and the negative sign in the Faraday law can turn that right side into the negative sign.
Google's New-Newsgroups censors AP posts and halted a proper archiving of author, but Drexel's Math Forum does not and my posts?in archive form is seen here: